Distinct role of heme oxygenase-1 in early- and late-stage intracerebral hemorrhage in 12-month-old mice. Issue 1 (January 2017) - Zhang, Zhen; Song, Yuejia; Zhang, Ze; Li, Danyang; Zhu, Hong; Liang, Rui; Gu, Yunhe; Pang, Yuxin; Qi, Jiping; Wu, He; Wang, Jian
Intracerebral hemorrhage (ICH) is a devastating form of stroke with high morbidity and mortality. Heme oxygenase-1 (HO-1), the key enzyme in heme degradation, is highly expressed after ICH, but its role is still unclear. In this study, we used an HO-1 inducer and inhibitor to test the role of HO-1 in different stages of ICH in vivo and in vitro. In the early stage of ICH, high HO-1 expression worsened the outcomes of mice subjected to the collagenase-induced ICH model. HO-1 increased brain edema, white matter damage, neuronal death, and neurobehavioral deficits. Furthermore, elevated HO-1 increased inflammation, oxidative stress, matrix metalloproteinase-9/2 activity, and iron deposition. In the later stage of ICH, long-term induction of HO-1 increased hematoma absorption, angiogenesis, and recovery of neurologic function. We conclude that HO-1 activation mediates early brain damage after ICH but promotes neurologic function recovery in the later stage of ICH.